Penelantaran Istri oleh Suami Merupakan Tindak Pidana - Mega Rachmasari Ristian Yunantika; Rochmani Rochmani (Fakultas Hukum Universitas Stikubank, 2021)
The harmony and integrity of the household can be disturbed if behavior and self-control cannot be controlled, the bad result is negative behavior, namely anger and quarrels which can lead to acts of domestic violence. Likewise, neglect of the household is not a new thing, because the fact is that it often occurs in the reality of society. This study aims to explain the factors that cause household neglect, to explain the legal consequences for the husband who has neglected his wife, and, to explain the efforts that must be made to prevent neglect in the household again. The method used in this research is a normative juridical approach and a descriptive analytical research specification, data collection using techniques such as literature study, interviews, and documentation. The data source that has been used is secondary data. The results of this research indicate the factors that cause household neglect are; do not provide a living, make dependence; the existence of a patriarchal culture in society; low education and knowledge of women as wives. The provisions of the Marriage Law stipulate that the husband must be responsible, if it is violated then legal sanctions will apply. In cases of household neglect, a solution is usually found not to be penalized and not to be fined. Efforts that must be made so that household neglect does not occur again is by car; there must be awareness, there needs to be religious guidance, it is not enough to just provide material but cannot educate his wife well, there must be mental development because a husband to become a leader must be able to lead his wife to a better direction. Legal consequences / sanctions for a husband who has neglected his wife can be punished with a maximum imprisonment of three years or a maximum fine of Rp. 15 million based on articles 49 and 50 of Law no. 23 of 2004 concerning PKDRT. Efforts that must be made so that neglect of the household does not occur again is by means of citizen awareness that neglect is a criminal act, so that law enforcement must continue so that people understand that neglect is a criminal act, from the aspect of marriage there must be socialization from the general public . Keywords: neglect, wife, violence, household, criminal.